Health Sector Budgetary Allocations and their Implications On Health Service Delivery and UHC in Uganda - Ssempala, Richard; Kintu, Francis; Okuda, Boniface; Ssengooba, Freddie; Bagonza, John; Tashobya, Christine K. (SPEED Initiative, 2019)
The health of Ugandans has improved over the last 2 decades as shown by various indicators1. Infant mortality rate declined from 94 to 43 deaths per 1,000 live births over the same period (1998-2018) while under-five mortality rate reduced from 149 to 64 deaths per 1,000 live births2. There has also been a reduction in maternal deaths with the maternal mortality ratio declining from 639 deaths per 100,000 live births in 1998 to 336 in 20163.The average number of children born by a Ugandan woman in her life time (fertility rate) declined from 6.9 in 1999 to 5.5 in 20164. However, people’s health is still poor as shown by the fact that the country is ranked 186 out of 191 WHO member states. Life expectancy at birth for Ugandans is still low estimated at 62.5 years. The common causes of illness include malaria and pneumonia (cough or cold) –contributing more than 50% of the OPD attendances. The number of malaria cases per 1,000 persons stood at 433 in 2016/175. HIV/AIDS prevalence among adults aged 15 to 64 is estimated at 6.2% -This corresponds to approximately 1.2 million people living with HIV. In addition there is increasing prevalence of non-communicable diseases like diabetes hypertension and cancer.